Open-hole and filled-hole failure envelopes of bfrp and gfrp: A comparative study - Sajid, Z. (Springer Science and Business Media Deutschland GmbH, 2020)
Open- and filled-hole analysis is essential in the calculation of allowable stresses of composite structures as open- and filled-hole strengths of a structure can be limiting factors. Considering the end of product life management, most companies are starting to replace traditional composite materials with green materials. One of the best options is to substitute glass fibers with basalt fiber. Basalt fibers are less costly than glass fibers. Importantly, basalt is a green material along with excellent recyclability. Therefore, this research aims to compare the BFRP and GFRP with respect to the open- and filled-hole laminates. In this research work, strain-based failure envelopes of open- and filled-hole laminates made up of E-glass, S2-glass, and basalt were compared and discussed. Classical laminate theory and Lekhnitskii solution were used to develop the failure envelopes. In addition, the effect of first ply failure (FPF) and last ply failure (LPF) on failure envelopes was also discussed. In longitudinal and transverse tensions, basalt fiber has large failure strains as compared to E-glass and has a reasonably comparable failure strains with S2-glass. In compression, basalt is better than E-glass and S2-glass. Â© Springer Nature Singapore Pte Ltd 2020.